Oral diet management for carcinoma at the base of tongue with radiotherapy and chemotherapy associated dysphagia: a case report - Ding, Zhen; Zhou, Lingmei; Jin, Kemei; Wu, Runjinxing; Gui, Yihua (Frontiers in Nutrition, 2023)
Introduction Tongue cancer is one of the common malignancy of the head and neck, and directly impacts chewing, swallowing, and other eating activities. Based on the evidence-based guidelines and clinical management, this paper presents nutrition management experience of a patient with tongue cancer who had a dysphagia and feeding reflux while undergoing radiotherapy and chemotherapy. Methods Nutritional risk screening and comprehensive nutritional assessment were performed based on the patient’s medical history, and personalized nutritional programs were developed under the guidance of the clinical pharmaceutical consensus of parenteral nutrition and nutritional treatment guidelines for patients with tumors during radiotherapy. For the management of oral feeding, the patient’s swallowing function was evaluated to manage oral feeding. Thickening powders were used to improve the consistency of the patient’s food, which successfully achieved oral feeding of the patient. Results The patient finally ate five meals a day by mouth, and energy requirements were met using industrialized nutritional supplements, and homogenized food was added in between the meals. The energy provided by enteral nutrition can reached approximately 60–75%. The patient’s weight and albumin levels had increased significantly at the time of discharge. Discussion The nutritional management of patients with dysphagia should be jointly managed by clinicians, nurses, nutritionists, and family members to effectively improve the quality of life (QOL) and nutritional status of patients. To ensure adequate nutritional supply, appropriate swallowing training may delay the deterioration of the chewing function and improve the eating experience of such patients.